Aspek Kinerja Keberlanjutan Terhadap Manajemen Aset Serta Dampaknya Pada Nilai Perusahaan Perbankan 10 Besar Di Indonesia - Mulyaningtyas, Mulyaningtyas (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2024)
The financial services sector provides comprehensive support to create sustainable economic growth by aligning economic, environmental and social interests in accordance with the sustainable finance work plan initiated by the Financial Services Authority. OJK in accelerating sustainable finance has realized it in the issuance of the Sustainable Finance Roadmap in 2015 - 2019 and continued in the second phase from 2020 to 2024. Almost 50% of banks in Indonesia representing 91% of Indonesia's total banking market assets show an increasing commitment to implementing sustainable finance, as measured by their Sustainability Reports. The aim of the research is to determine the influence of economic, environmental and social aspects on asset management and their impact on company value. The analysis method used is quantitative descriptive, using secondary data in the form of sustainability reports and financial statements obtained through www.idx.co.id. with purpose sampling techniques obtained by 10 bank entities. The data was processed by multiple regression techniques with intervening variables of path analysis. The results of the study Aspects of sustainability performance do not directly affect asset management and company value, while aspects of sustainability performance through asset management have an indirect effect on and company value.